Biochemical markers of bone turnover in patients with spinal metastases after resistance training under radiotherapy – a randomized trial. Issue 1 (December 2016) - Rief, Harald; Omlor, Georg; Akbar, Michael; Bruckner, Thomas; Rieken, Stefan; Förster, Robert; Schlampp, Ingmar; Welzel, Thomas; Bostel, Tilman; Roth, Heinz; Debus, Jürgen
Abstract Background To compare the effects of resistance training versus passive physical therapy on bone turnover markers (BTM) in the metastatic bone during radiation therapy (RT) in patients with spinal bone metastases. Secondly, to evaluate an association of BTM to local response, skeletal-related events (SRE), and number of metastases. Methods In this randomized trial, 60 patients were allocated from September 2011 to March 2013 into one of the two arms: resistance training (Arm A) or passive physical therapy (Arm B) with thirty patients in each arm during RT. Biochemical markers such as pyridinoline (PYD), desoxy-pyridinoline (DPD), bone alkaline phosphatase (BAP), total amino-terminal propeptide of type I collagen (PINP), beta-isomer of carboxy-terminal telopeptide of type I collagen (CTX-I), and cross-linked N-telopeptide of type I collagen (NTX) were analyzed at baseline, and three months after RT. Results Mean change values of PYD and CTX-I were significantly lower at 3 months after RT (p  = 0.035 andp  = 0.043) in Arm A. Importantly, all markers decreased in both arms, except of PYD and CTX-I in arm B, although significance was not reached for some biomarkers. In arm A, the local response was significantly higher (p  = 0.003) and PINP could be identified as a predictor for survivors (OR 0.968, 95%CI 0.938–0.999, p  = 0.043). BAP (OR 0.974, 95%CI 0.950–0.998, p  = 0.034) and PINP (OR 1.025, 95%CI 1.001–1.049, p  = 0.044) were related with an avoidance of SRE. Conclusions In this group of patients with spinal bone metastases, we were able to show that patients with guided resistance training of the paravertebral muscles can influence BTM. PYD and CTX-I decreased significantly in arm A. PINP can be considered as a complementary tool for prediction of local response, and PINP as well as BAP for avoidance of SRE. Trial registration Clinical trial identifier NCT 01409720. August 2, 2011.